2020
DOI: 10.1097/j.jcrs.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Development of low laser energy levels in small-incision lenticule extraction: clinical results, black area, and ultrastructural evaluation

Abstract: Purpose: To evaluate the outcomes of 4 low laser energy levels after small-incision lenticule extraction (SMILE) surgery. Setting: Zhongshan Ophthalmic Center, Guangzhou, China. Design: Prospective randomized clinical trial. Methods: This study evaluated consecutive patients who had SMILE to correct myopia or myopia with astigmatism. Eyes were placed into groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…However, the incidence of black areas in our study eyes was 2.7% (ESM File 1). The incidence of BS determined in our study differs greatly from that reported in earlier studies, but the incidence of black areas is consistent with earlier studies, ranging from 0.33% to 11% [9,24,25]. Therefore, we believe that the terms 'black spots,' 'black areas,' or 'black islands' may not have been used consistently in previous publications [26,27].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, the incidence of black areas in our study eyes was 2.7% (ESM File 1). The incidence of BS determined in our study differs greatly from that reported in earlier studies, but the incidence of black areas is consistent with earlier studies, ranging from 0.33% to 11% [9,24,25]. Therefore, we believe that the terms 'black spots,' 'black areas,' or 'black islands' may not have been used consistently in previous publications [26,27].…”
Section: Discussionsupporting
confidence: 71%
“…Hence, we recognized that the BS are the tissue bridges between laser spots. This phenomenon was indirectly confirmed by Lin et al who estimated the black areas of four levels of low laser energy for SMILE surgery and found that the lowest energy used had the largest area of BS [24]. The surface quality of scanning may be mainly determined by two factors: (1) the distance of laser spots and the delivered energy of per pulse; and (2) tissue reaction for photo disruption [28,29].…”
Section: Discussionmentioning
confidence: 73%
“…As for black spots, in our experience black spots were observed as isolated punctual micro-regions, and they seemed more related to debris at the cornea-laser interface than to instability of the laser energy. 29 We think that one reason why they did not interfere with the dissection can be the fact that ATOS is using a relatively high Repetition Rate, in the MHz regime, associated with a low energy per pulse with dense overlap. 30 Thus, many tiny microbubbles are created close together; probably stochastically homogenizing the ease of dissection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a mismatch of spot distance and energy levels may cause overlapping of the cavitation bubbles, and the resulting opaque bubble layer may impair the subsequent laser beam, leading to surface microirregularities. 9 Furthermore, higher laser energy levels were reported to be associated with greater keratocyte death and inflammation in FS-LASIK. 20 Notably, not only was the laser pulse energy higher in Group 1 but the cumulative energy as well.…”
Section: Discussionmentioning
confidence: 99%
“…8 In contrast, pulse energy that is too low can induce black areas during treatment, which may hinder the surgical separation of the lenticule, causing postoperative corneal edema and impaired visual outcomes. 9 Corneal microirregularities can result in straylight, and 1 study showed that the thickness of new irregular stromal tissue formed after photorefractive keratectomy is related to increased objective corneal scattering. 10 Different surgical techniques induce different cellular responses; for example, photorefractive keratectomy increases transforming growth factor b1 expression in keratocytes, resulting in corneal haze.…”
mentioning
confidence: 99%